Raggedy Ann and Andy and the nice police officer - Gruelle, Johnny; Gruelle, Johnny, 880-1938; Palmer, Jan Janice) (New York : Simon & Schuster Books for Young Readers, 1999)
Raggedy Ann and her brother keep an innocent man from being arrested and help reform a greedy magician.
Accelerated Reader AR
Keywords: Dolls -- iction; Police -- iction; Magic -- iction